Communication in the evolving world of case management. - Keigher, Sharon M. (Health & Social Work, 2000)
Recent developments in case management demonstrate some of the communication challenges—the diversity of electronic communication tools and computerized record keeping techniques—to social work practice. Although some social workers claim that case management is not new, the processes and needs of managed care organizations have so confused some social workers that they consider the “science” of case care beyond them. Yet others have become so infatuated with data, computerized systems, and their outputs that they have forgotten the people the systems were supposed to help. Social work is creating new knowledge that demonstrates its fitness for this essential health work, but social care workers could do a better job of communicating this to the public.